Quelques remarques sur la désambiguïsation des sens du verbe mettre - Gabrysiak, Katarzyna (Neophilologica, 2008)
This study analyses the use of the French verb mettre with the aim of disambiguating their meanings. The process consists in finding every possible meaning of the word by analyzing contexts in which it might appear. This stage constitutes an integral part of creating a Polish-French and French-Polish electronic dictionary and exemplifies the methodology of object-oriented approach proposed by Professor W. Banyś. The analysis is based on the information taken from Le Grand Robert de la Langue Française, Le Trésor de la Langue Française. After analyzing all contexts in which the verb has appeared and after specifying the object classes for each its use of the verb, the author gives its Polish equivalent. Twenty eight Polish equivalents of the French verb mettre are presented.